MoS2 and CdMoS4 nanostructure-based UV light photodetectors - Pawar, Mahendra S.; Kadam, Sunil R.; Kale, Bharat B.; Late, Dattatray J. (Nanoscale Advances, 2021)
We have developed MoS2 nanosheets and CdMoS4 hierarchical nanostructures based on a UV light photodetector. The surface morphologies of the as-prepared samples were investigated via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The performance parameters for the present photodetectors are investigated under the illumination of UV light having a wavelength of similar to 385 nm. Upon the illumination of UV light, the CdMoS4-based photodetector device showed a better response to UV light compared to the MoS2 device in terms of photoresponsivity, response time (similar to 72 s) and recovery time (similar to 94 s). Our results reveal that CdMoS4 hierarchical nanostructures are practical for enhancing the device performance.